Pengaruh Financial Flexibility, Profitabilitas, dan Financial Leverage terhadap Nilai Perusahaan dengan Firm Size Sebagai Variabel Pemoderasi - Sari, Prisilia; Willim, Andre Prasetya (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to examine the influence of financial flexibility, profitability, and financial leverage on company value using company size as a moderating variable. Property and real estate companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024 were the subjects of this study. A total of 322 data items met the requirements for purposive sampling. This study aims to examine the influence of financial flexibility, profitability, and financial leverage on company value using company size as a moderating variable. Property and real estate companies listed on the Indonesia Stock Exchange (IDX) between 2020 and 2024 were the subjects of this study. A total of 322 data items met the requirements for purposive sampling. According to the findings, business value is negatively affected by financial flexibility, but not affected by profitability or financial leverage. It has been shown that business size increases the impact of financial flexibility on company value, but cannot reduce the interaction between profitability and financial leverage. It is hoped that this study will increase scientific understanding of the variables that affect company value and assist investors and management.